Effect of sintering temperature on dielectric properties, and microstructure of Ni(₀.₃)Zn(₀.₇)Fe₂O₄ - Mat, Mohd Noor (2017)
A series of ferrite material with Ni(0.3)Zn(0.7)Fe2O4 composition have been prepared by the solid state reaction method and sintered at a temperature range of 673 to 1623 K with an interval of 100 K. A total of ten samples was synthesized for this research work. After the samples were sintered, the surface morphology, structure of each sample, density, dielectric and conductivity measurement were made first and then the samples were re-sintered at an increase temperature of 50 K so that the sintered temperatures were 723, 823,923, 1023, 1123, 1223, 1323, 1423, 1523 and 1623 K. The surface morphology, structure of each sample, density, dielectric and conductivity measurement were made once again after next sintering. Samples were confirmed mixture of crystal phase when sintered under 1173 K and single crystals were formed when sintered above 1173 K via X-ray diffraction measurement. FESEM diagram showed that grain size increased slowly when sintered below 1073 K from 32 to 253 nm and increase drastically when sintered above 1073 K from 1880 to 7590 nm. EDX technique or EDS has been used to determine oxide constituent composition of samples. There was no noticeable change in density for samples sintered below 1173 K and density increased drastically when samples sintered more than 1173 K. Relative dielectric permittivity and loss factor had been measured in frequency ranges from 0.01 to 3 MHz and in the temperature range 303 to 473 K. Experimental data are simulated to a model proposed by Havriliak-Negami (HN) which consists of a combination of several HN functions and a real capacitor and conductance. Relative dielectric permittivity for all samples decrease in the range from 1.5 x 106 to 5 with increased frequency from 10-2 to 3 MHz and decrease with increase of 1000/T until the temperatures range from 363to 403 K and then increase with increase of 1000/T for all fixed frequencies. These changes are due to dielectric relaxation and electron hopping interaction. At low frequency (below 100 Hz) relative dielectric permittivity is dominated by surface charge polarization and the values are in between 104 to 1.5 x 106. Dipole occurs in frequency ranges from 100 to 100 kHz with value in between 50 to 150 while electronic polarization occurs above 100 kHz with values in between 5 to 10. Generally relative dielectric permittivity decreases with increasing of frequency and the same trend occurs as sintered temperature increase. This phenomenon can be explained based on the changes microstructures of the samples (resistance of grain and grain boundary). The variation of conductivity versus frequency consists of three parts which are at high frequency, the conductivity depends on the power law, at the middle variation depends on polarization and at low frequency, the conductivity is independent with frequency. Apart from that conductivity at low frequency also increases when sample temperature increase and the value of conductivities of all sample sintering in between 10-8 to 10-4S/m. Conductivity phenomenon which occurred in this sample is due to continuous hopping of charge carrier. Impedance spectroscopy has been used in this study to further analyse the conductance of the sample, especially to determine the activation energy. The values of conductance of grains and grain boundary were determined to be in the range of 0.01 to 10 mho and 10-9 to 10-5 mho respectively. DC activation energy is obtained from the variation of resistivity at low frequency in temperatures range between 303 to 473 K. The values of activation energy in the intrinsic part determined from the high temperature slope region of all sintering temperatures are in between 0.09 to 0.62 eV and the value of extrinsic part determined from the low temperature slope region are in between 0.11 to 0.48 eV. The conductivities decrease when 1/T increases in both samples phase at high temperature region, meanwhile the conductivities increase with no special trends when 1/T increases in the low temperature region of the mixture of crystal phase sample and the conductivities decreases linearly when 1/T increases in the low temperature region at single crystal phase samples except sample with a sintering temperature of 1623 K. The variations of conductivities versus 1/T increases when frequency of external electric field increases. The charges moving in an AC conductivity of the sample are dominant by hopping meanwhile the charges moving in the DC conductivity of the sample is dominated by the free electron. The conductance of these samples have been studied in range 1 nS to 10 μS. At the same time, AC activation energy at various fixed frequencies was determined and the value is in the range of 0.14 to 0.86 eV for sample sintering temperatures from 673 to 1123 K and 0.11 to 0.75 eV for sample sintering temperatures from 1173 to 1623 K. The trend of AC activation energies for all samples are in the decreasing trend when the fixed frequency of external electric field is increased.